Rapid Natural Decline of Upper Montane Forests in the Swedish Scandes - Kullman, Leif; Högberg, Nils (ARCTIC, 1989)
Unprecedented needle loss of mature forest stands occurred in natural Swedish montane forests during 1987. Pine (Pinus sylvestris L.) and spruce (Picea abies [L.] Karst.) needles turned reddish-brown during the spring and early summer. An intensive study within a severely damaged pine population indicated that damage was primarily due to a coincidence of shallow snow cover and severe cold from mid-December 1986 to mid-January 1987. This resulted in unusually cold soils and late thawing of the soils. Acute drought stress then developed in late winter during a period of sunny weather and great diurnal temperature ranges. Thus, the study supports the classical theory of winter desiccation as an important component in population ecology of cold marginal forests in this part of the world. Historical data indicate that the present kind of damage was more frequent prior to the present century. It is suggested that cold-induced dieback is an important, but often overlooked, disturbance process in northern boreal forests relevant to Holocene forest history.Key words: forest damage, montane forests, Pinus sylvestris L., winter desiccation, disturbance, Holocene forest history, Sweden Mots clés: dommages àla forêt, forêts montagneuses, Pinus sylvestris L., dessèchement hivernal, perturbation, histoire de la forêt de l’holocène, Suède